Antibacterial activity of vegetal extracts against serovars of Salmonella - Voss-Rech,Daiane (2011)
in vitro antibacterial activity of 21 hydroethanolic vegetal extracts was assessed against 20 serovars of Salmonella. Regarding the tested extracts, 85.7% of them presented antibacterial activity. The six active extracts which showed activity on the largest number of serovars and the extract of Eucalyptus sp. were submitted to the determination of Minimum Inhibitory Concentration (MIC) and Minimum Bactericidal Concentration (MBC). Of these, six extracts showed bacteriostatic and bactericidal activity with MIC and MBC for Punica granatum (pomegranate) from 20 and 60mg mL-1, for Eugenia jambolana (rose apple) from 40 and 240mg mL-1, Eugenia uniflora (surinam cherry) from 80 and 240mg mL-1, Caryophyllus aromaticus (clove) from 10 and 60mg mL-1, Psidium araca from 30 and 320mg mL-1 and Eucalyptus sp. from 40 and 160mg mL-1. Achyrocline satureioides (macela) presented only bacteriostatic potential and MIC from 160mg mL-1. Caryophyllus aromaticus, Eucalyptus sp., and Psidium araca presented the best results for bactericidal activity, inhibiting, respectively, 84.2%, 42.1%, and 17.6% of Salmonella's serovars. The activity of each extract varied for different serovars; S. London presented resistance to the six extracts in MBC, while S. Pullorum was the most susceptible serovar.